TI_GERICHTE 12.2006.150 vom 15. Mai 2007 , società anonima cancellata a RC - domanda di reiscrizione - condizioni - TI Tribunale d'appello (2007)
società anonima cancellata a RC - domanda di reiscrizione - condizioni